Tiimipelaaja, joka bongaa pienimmätkin kirjoitusvirheet! Mitä työpaikkailmoitukset kertovat siitä, kenelle ja missä kääntäjän tehtäviä Suomessa on tarjolla? - Hjort Minna (Finland, 2025)
Job advertisement analyses provide us with information about job opportunities available in a given profession at a given point in time. Furthermore, they offer a window to the requirements, preferences and expectations of employers in a given market. Such research can also produce valuable data for the planning of training programmes, allowing educators to provide students with up-to-date information about a field and to adjust to market needs where necessary. This paper presents the results of an analysis of 120 Finnish job advertisements for in-house translators. The analysis supports the industry view of translators working with Swedish being in high demand and confirms previous research on the diversity of employers still employing translators. The results indicate that Finnish employers value university education, work experience, and technological competence, and seek employees who meet the needs of the overall job culture and market: flexible, stress tolerant, independent but team-oriented; excellent communicators both orally and in writing.
MikaEL16: XIX Kääntämisen ja tulkkauksen tutkimuksen symposiumi